2015
DOI: 10.1080/13548506.2015.1062900
|View full text |Cite
|
Sign up to set email alerts
|

Time perspective, socioeconomic status, and psychological distress in chronic pain patients

Abstract: Time perspective (TP) is a fundamental dimension of the psychological construction of time. It refers to a subjective experience and can be defined as the relationship that individuals and groups have with the present, past, and future. Studies have shown that it is interesting to take into account TP in the field of health, especially for the study of the psychological distress (PD) of individuals faced with aversive situations. We conducted a research, which aimed to explore the relationship between TP and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
2
18
0
5
Order By: Relevance
“…The present study did not assess delay discounting, but rather focused solely on time perspectives. Although delay discounting may be a relevant issue for FSWs, the present study focused on time perspective because it is influenced by external forces (e.g., life stressors and events) (Dany et al, 2016;Holman et al, 2016), and thus may be more amenable to change through psychological and cognitive interventions. In contrast, delay discounting, which has been described as internal and a personality trait (Albein-Urios et al, 2014;Anokhin et al, 2015) may be more difficult to change in the context of ongoing drug use (Hulka et al, 2015;Teuscher & Mitchell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The present study did not assess delay discounting, but rather focused solely on time perspectives. Although delay discounting may be a relevant issue for FSWs, the present study focused on time perspective because it is influenced by external forces (e.g., life stressors and events) (Dany et al, 2016;Holman et al, 2016), and thus may be more amenable to change through psychological and cognitive interventions. In contrast, delay discounting, which has been described as internal and a personality trait (Albein-Urios et al, 2014;Anokhin et al, 2015) may be more difficult to change in the context of ongoing drug use (Hulka et al, 2015;Teuscher & Mitchell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In our exploratory analyses, our study population was similar to the profile of patients suffering from chronic pain in France [ 77 ], Germany [ 78 ], the United Kingdom [ 2 ], Canada [ 79 ], or the United States [ 74 , 80 , 81 ]—predominantly female, middle-aged, active population of lower socioeconomic status (precariousness, employment status, level of education), with pain lasting more than 5 years and suffering from psychological distress and from fairly severe chronic pain that has a significant impact on their lives (92% with moderate-to-severe pain, 20% with high impact chronic pain [ 74 ] and 43% with sleep disorders, such as awakenings due to pain at least once a night), mainly treated by antidepressants, and weak opioids. Interestingly, most did not simultaneously explore sociodemographic, psychological, pain disorders, and treatments characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, positive past was significantly and directly correlated with age; therefore, attitudes toward the past became more negative with increasing age. Time perspective is considered one of the important psychosocial factors that are effective on psychological distress in MS patients (13). A study with MS patients showed that they were ready to assess and to prepare for possible adverse outcomes of the illness.…”
Section: Discussionmentioning
confidence: 99%
“…(12). This can be influenced by chronic disease and lead to certain disorders in the affected individual (13).…”
Section: Introductionmentioning
confidence: 99%